The nursery against the complications of hypothermia in the immediate post-operative - Larissa Pereira Martins, Nery Oliveira Junior, Fernando Riegel, Deise Simão Arregino (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.8168-73